2010
DOI: 10.4271/2010-01-0571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Boosting Strategies for Homogeneous Charge Compression Ignition Engines - A Modeling Study

Abstract: Boosted Homogeneous Charge Compression Ignition (HCCI) has been modeled and has demonstrated the potential to extend the engine's upper load limit. A commercially available engine simulation software (GT-Power®) coupled to the University of Michigan HCCI combustion and heat transfer correlations was used to model a 4-cylinder boosted HCCI engine with three different boosting configurations: turbocharging, supercharging and series turbocharging. The scope of this study is to identify the best boosting approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The intake and exhaust manifold absolute pressures are set at 1, 1.5 and 2 bar for the boost sweep. For turbocharged HCCI, the exhaust manifold pressures are typically much greater than the intake manifold pressures; 1114 however, this work makes a modeling simplification by setting the intake and exhaust pressures equal to each other. The amount of fuel injected is increased with boost to hold the mixture composition constant in terms of fuel-to-oxygen equivalence ratio ( ϕ FO ), fuel-to-charge equivalence ratio ( ϕ ), residual gas fraction (RGF) and oxygen mole percentage ( χ O 2 ).…”
Section: Boost Sweep—simulation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intake and exhaust manifold absolute pressures are set at 1, 1.5 and 2 bar for the boost sweep. For turbocharged HCCI, the exhaust manifold pressures are typically much greater than the intake manifold pressures; 1114 however, this work makes a modeling simplification by setting the intake and exhaust pressures equal to each other. The amount of fuel injected is increased with boost to hold the mixture composition constant in terms of fuel-to-oxygen equivalence ratio ( ϕ FO ), fuel-to-charge equivalence ratio ( ϕ ), residual gas fraction (RGF) and oxygen mole percentage ( χ O 2 ).…”
Section: Boost Sweep—simulation and Resultsmentioning
confidence: 99%
“…9 In addition to experimental studies, 69 a number of simulation studies have been performed to assess the requirements of boosted HCCI turbomachinary. 1014 Typically, boosted HCCI demands higher intake pressures at similar conditions than conventional engines due to greater dilution required to beat the NOx emission limit. 7 On the other hand, intake boost for turbocharged HCCI comes at a significant pumping penalty.…”
Section: Introductionmentioning
confidence: 99%
“…Mamalis et al 1,8 have presented detailed literature reviews in previous publications regarding VVA and boosting for HCCI engines. Some key findings will be summarized here for completeness.…”
Section: Vva and Boostingmentioning
confidence: 99%
“…A study of boosting strategies for HCCI performed by Mamalis, et al, [14] concluded that a staged turbocharger system extends the load range at 2000 rev/m. The additional pumping work of the boost system reduced the brake efficiency, however.…”
Section: Introductionmentioning
confidence: 98%